Improving Interpersonal Communication Skills In Forming Organizational Commitment At Telekomedika Vocational High School In Bogor - R. Nur Amalia; Sri Sundari; Fernandez Hutagalung; Freddy Johanis Rumambi; Marisi Pakpahan (Management Dynamics: International Journal of Management and Digital Sciences, 2024)
Interpersonal communication is communication between a communicator and a communicant. This type of communication is considered the most effective in changing someone's attitude, opinion or behavior, because of its dialogic nature in the form of a conversation. Commitment to the organization means the level of trust and acceptance of the workforce towards the goals of the organization and the desire to remain in the organization which is ultimately reflected in the problems above. This research has several objectives, namely to analyze interpersonal communication skills between school principals and Telekomedika Vocational School teachers and to analyze the organizational commitment of Telekomedika Vocational School teachers. This research uses descriptive qualitative, with the data collected mostly in the form of words or images rather than numbers. The subjects in this research were leaders, teachers and staff at Bogor Telekomedika Vocational School. The research carries out analysis of the data obtained through interviews and other documents by combining and selecting data that is close to suitability related to the research study. The results of the research show that interpersonal communication can be done by improving communication so that they are more motivated to complete the work given by the organization, developing a positive attitude and attention to work in each teacher, setting work goals and trying to improve teachers' work knowledge. It is known that teachers' organizational commitment at Telekomedika Vocational Schools means that teachers as educators and instructors should have a commitment to the organization as a process that is not only limited to creating new ideas or thoughts. The idea must be implemented through an adoption process, and adoption is the decision to use commitment to the organization as a whole as the best course of action.